An Investigation of Container Loading Problem Dealing with Irregular Shape Shipment - Chang, Xinyue; Zhang, Haiyan H. (International Journal of Industrial Engineering and Management, 2015)
Container loading problem (CLP) is a category of problems that describing the scenarios of packing shipments into containers. It has been discussed in the fields of logistics, industrial engineering, transportation (civil) engineering, and operational management for many years. However, handling irregular shape shipment was not been investigated in-depth, such as algorithms of overlap searching, schemes of placing items, real world constraints, and damage control. This paper is dedicated to investigate and understanding the complexity and difficulties of the CLP involving irregular shape shipment, especially when closely related to industrial conditions. Beyond the previous works, the problem statement in this paper is formed with the idea of reflecting the real world scenarios and illuminating future research direction. In order to maximize the benefit of this paper to the industries, multiple methods and candidates are proposed that are collected from other fields. This paper includes overview of the factors related to irregular shape CLP that is worthy to concern while working on the next generation of great CLP approaches, particularly in handling irregular shape shipments. Article history: Received (24.05.2015); Revised (27.06.2015); Accepted (03.07.2015)